WHEN STATE REGULATES HUSBAND'S IDAH: Pros and Cons among Penghulu in Yogyakarta - Permata, Cindera (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2023)
In 2021, the Ministry of Religious Affairs issued a policy concerning the prohibition of husbands remarrying (another woman) during the wife waiting period (idah). This policy evoked both pros and cons. This study aims to investigate the emergence of this policy and analyze the responses from the marriage registrars (penghulu) at the Office of Religious Affairs (KUA). Taking place in Yogyakarta, this research constitutes fieldwork employing a socio-legal approach. Data were collected through in-depth interviews with the penghulu. The research reveals that the policy was fiercely motivated by three factors: firstly, the occurrence of concealed polygamous marriages during the idah period; secondly, the endeavor to actualize the wisdom of idah associated with the opportunity to reconcile (ruju') within the (on-going broken) marriage; and thirdly, the desire toward the protection of women. Some marriage registrars supported this policy, citing arguments aligned with its content. Conversely, others perceive that it is too far distorting fiqh and deemed incompatible with the National Marriage Law. Moreover, it was observed that penghulu mostly refused to register marriages for husbands during the idah period, although a small minority accepted such registrations.[Abstrak: Pada 2021, Kementerian Agama mengeluarkan kebijakan terkait pelarangan suami menikah dalam masa idah istri. Kebjakan ini menimbulkan pro dan kontra di berbagai kalangan, baik eksternal maupun internal lembaga tersebut. Penelitian ini bertujuan mengkaji konteks mengapa kebijakan tesebut muncul dan bagaimana respon dari para penghulu KUA. Mengambil seting di Kota Yogyakarta, penelitian ini merupakan penelitian lapangan dengan pendekatan sosiologi hukum. Data dikumpulkan melalui wawancara mendalam dengan para penghulu. Penelitian ini mengungkap bahwa lahirnya kebijakan tersebut dimotivasi oleh tiga faktor, yaitu, fenomena poligami terselubung yang dilakukan dalam masa idah, upaya Kementerian Agama merealisasi hikmah idah yang terkait dengan kesempatan kembalinya pasangan ke dalam perkawinan, dan pemberian perlindungan dan kesetaraan terhadap perempuan. Atas kebijakan tersebut, sebagian penghulu mendukung dengan argumen yang sesuai dengan isi kebijakan. Sedangkan sebagian yang lain menolak karena menganggap hal tersebut terlalu jauh dari norma fikih dan dianggap tidak sejalan dengan UU Perkawinan. Selain itu, ditemukan juga bahwa penghulu telah menolak pendaftaran pernikahan suami dalam masa idah. Namun sebagian kecil ada yang menerima.]